As eleições no Estado Novo : as eleiçõe presidenciais de 1949 e 1958 - Ferreira, Ana Sofia (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Notwithstanding the fact that it was a dictatorship, the Estado Novo (‘New State’) consecrated in the Constitution the realisation of presidential and legislative elections and also elections to the Juntas de Freguesia (Local Halls), given that only the popular vote could provide it with the internal and external legitimisation it needed. However, the electoral results were always controlled in order to guarantee the victory of União Nacional’s (‘National Union’) candidate or list and all the elections were fraudulent. The presidential elections of 1949 and 1958 were two of these important moments to Portugal, in which the people could have voted and decided the country’s future, but instead oppression, censorship, violence and fraud marked the electoral campaign and determined the voting, guaranteeing the victory of the Situation candidates and the defeat of the Opposition ones, despite the fact that the latter had, unequivocally, the support of the majority of the population.